Secondary Fracture Prevention: Consensus Clinical Recommendations from a Multistakeholder Coalition. (1st December 2019) - Conley, Robert B; Adib, Gemma; Adler, Robert A; Åkesson, Kristina E; Alexander, Ivy M; Amenta, Kelly C; Blank, Robert D; Brox, William Timothy; Carmody, Emily E; Chapman‐Novakofski, Karen; Clarke, Bart L; Cody, Kathleen M; et al.
ABSTRACT: Osteoporosis‐related fractures are undertreated, due in part to misinformation about recommended approaches to patient care and discrepancies among treatment guidelines. To help bridge this gap and improve patient outcomes, the American Society for Bone and Mineral Research assembled a multistakeholder coalition to develop clinical recommendations for the optimal prevention of secondary fracture among people aged 65 years and older with a hip or vertebral fracture. The coalition developed 13 recommendations (7 primary and 6 secondary) strongly supported by the empirical literature. The coalition recommends increased communication with patients regarding fracture risk, mortality and morbidity outcomes, and fracture risk reduction. Risk assessment (including fall history) should occur at regular intervals with referral to physical and/or occupational therapy as appropriate. Oral, intravenous, and subcutaneous pharmacotherapies are efficacious and can reduce risk of future fracture. Patients need education, however, about the benefits and risks of both treatment and not receiving treatment. Oral bisphosphonates alendronate and risedronate are first‐line options and are generally well tolerated; otherwise, intravenous zoledronic acid and subcutaneous denosumab can be considered. Anabolic agents are expensive but may be beneficial for selected patients at high risk. Optimal duration of pharmacotherapy is unknown but because the risk for second fractures is highest in the early post‐fracture period, prompt treatment is recommended. Adequate dietary or supplemental vitamin D and calcium intake should be assured. Individuals being treated for osteoporosis should be reevaluated for fracture risk routinely, including via patient education about osteoporosis and fractures and monitoring for adverse treatment effects. Patients should be strongly encouraged to avoid tobacco, consume alcohol in moderation at most, and engage in regular exercise and fall prevention strategies. Finally, referral to endocrinologists or other osteoporosis specialists may be warranted for individuals who experience repeated fracture or bone loss and those with complicating comorbidities (eg, hyperparathyroidism, chronic kidney disease). © 2019 American Society for Bone and Mineral Research.